Development of an expert system for fault diagnosing of washing machines using Delphi 7 - Bagus Dwi Cahyono; Dias Eka Kusuma (Jurnal Mantik, 2024)
An expert system is a system that tries to adopt human knowledge into washing machines, so that users can solve problems as experts usually do, and a good expert system is designed to be able to solve a particular problem by imitating the work of experts. Currently handling customer complaints to technicians about fault of washing machines takes quite a long time, and for each handling it takes quite a long time. This system aims to diagnose fault and provide information on repair solutions that can be carried out. This expert system uses the forward chaining method and literature study in Delphi. Based on testing this expert system, it shows that this expert system is able to help solve problems effectively